IL-37 Is a Novel Proangiogenic Factor of Developmental and Pathological Angiogenesis. Issue 12 (December 2015) - Yang, Tianshu; Lin, Qing; Zhao, Mengmeng; Hu, Yongguang; Yu, Ying; Jin, Jiayi; Zhou, Hongyan; Hu, Xiao; Wei, Rongbin; Zhang, Xuetao; Yang, Xiaoping; Liu, Gaoqin; et al.
Abstract : Objective—: Angiogenesis is tightly controlled by growth factors and cytokines in pathophysiological settings. Interleukin 37 (IL-37) is a newly identified cytokine of the IL-1 family, some members of which are important in inflammation and angiogenesis. However, the function of IL-37 in angiogenesis remains unknown. We aimed to explore the regulatory role of IL-37 in pathological and physiological angiogenesis. Approach and Results—: We found that IL-37 was expressed and secreted in endothelial cells and upregulated under hypoxic conditions. IL-37 enhanced endothelial cell proliferation, capillary formation, migration, and vessel sprouting from aortic rings with potency comparable with that of vascular endothelial growth factor. IL-37 activates survival signals including extracellular signal-regulated kinase 1/2 and AKT in endothelial cells. IL-37 promoted vessel growth in implanted Matrigel plug in vivo in a dose-dependent manner with potency comparable with that of basic fibroblast growth factor. In the mouse model of retinal vascular development, neonatal mice administrated with IL-37 displayed increased neovascularization. We demonstrated further that IL-37 promoted pathological angiogenesis in the mouse model of oxygen-induced retinopathy. Conclusions—: Our findings suggest that IL-37 is a novel and potent proangiogenic cytokine with essential role in pathophy siological settings. Abstract : Supplemental Digital Content is available in the text.